A preparation method of N-doped Zn-MOF derived carbon skeleton material and supercapacitor

By constructing and doping nitrogen-doping Zn-MOF carbon skeleton materials, the problem of insufficient capacitance performance of existing carbon materials is solved, and the high specific capacitance and rate performance is improved. It is suitable for miniaturized electronic products and remains stable under deformation conditions. .

CN115206695BActive Publication Date: 2024-12-24ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210946341.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-08
Publication Date
2024-12-24
Estimated Expiration
2042-08-08

AI Technical Summary

Technical Problem

The existing carbon materials have insufficient capacitance performance in supercapacitors, which cannot meet the increasingly expanding energy demands of modern society. The synergy between high conductivity, high specific surface area, graded porosity and heteroatom doping is difficult to compatible, resulting in the design And the development of high-performance capacitive carbon materials faces huge challenges.

Method used

Zn-MOF derived carbon skeleton material with high specific surface area, graded porosity and rich active sites was prepared by carbonization and urea nitrogen doping. , urea is used as a nitrogen source and activator to increase the pore size and specific surface area and improve capacitance performance.

Benefits of technology

It realizes the excellent capacitance performance of supercapacitors, provides high specific capacitance and good rate performance, is suitable for miniaturized electronic products applications, and maintains stable capacitance performance under different deformation conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115206695B_ABST
    Figure CN115206695B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of carbon materials, and specifically relates to a preparation method of an N-doped Zn-MOF-derived carbon skeleton material and a supercapacitor. The preparation method of the N-doped Zn-MOF-derived carbon skeleton material of the present invention comprises the following steps: 1) reacting a zinc source and an organic ligand in a solvent to obtain Zn-MOF; 2) calcining Zn-MOF at 700-950° C. under a protective atmosphere to obtain Zn-MOF-C; 3) mixing Zn-MOF-C and urea, and calcining at 700-900° C. to obtain an N-doped Zn-MOF-derived carbon skeleton material Zn-MOF-CN. The N-doped Zn-MOF-derived carbon skeleton material of the present invention is a layered structure composed of graphene nanosheets, which has a large specific surface area, a large graded porosity, contains N atom doping, has excellent capacitance performance, and the obtained supercapacitor also has excellent capacitance performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to a preparation method of an N-doped Zn-MOF derived carbon skeleton material and a supercapacitor. Background Art

[0002] From the perspective of charge storage mechanism, supercapacitors are divided into three categories: electric double layer capacitors (EDLCs), pseudocapacitors (PCs), and hybrid capacitors. Among them, EDLCs are widely used due to their high power density, stable cycle life, low cost, and maintenance-free characteristics. Porous carbon-based materials, such as activated carbon (AC), carbon nanotubes (CNTs), and reduced graphene oxide (rGO), have been widely studied as electrodes in EDLCs due to their large specific surface area, good pore structure, and high conductivity. Despite this, commercial carbon electrodes in EDLCs still cannot provide high specific capacitance and need to be further improved to meet the ever-expanding energy needs of modern society. The capacitive performance of EDLCs-type carbon materials is determined by the synergistic effect of four key factors: high conductivity, high specific surface area, hierarchical porosity, and heteroatom doping. The above four important factors show strong interactions, but each factor is sometimes incompatible. Therefore, it remains a huge challenge to design and develop carbon materials with high performance capacitance for EDLCs.

[0003] MOFs have attracted much attention as attractive precursors for the preparation of porous carbon electrode materials for EDLCs. Li et al. (Li Z.-X., Yang B.-L., Zou K.-Y., et al. Novel porous carbon nanosheet derived from a 2D Cu-MOF: Ultrahigh porosity and excellent performances in the supercapacitor cell [J]. Carbon, 2019, 144: 540-548.) prepared porous carbon nanosheets 2D Cu-MOF by carbonization and activation. -1 When the concentration of F g is 260.5, it provides a maximum of 260.5 F g in 6 M KOH solution. -1Duan et al. (Duan H.-H., Bai C.-H., Li J.-Y., et al. Temperature-Dependent Morphologies of Precursors: Metal–Organic Framework-Derived Porous Carbon for High-Performance Electrochemical Double-Layer Capacitors [J]. Inorganic Chemistry, 2019, 58(4): 2856-2864.) reported a cabbage-like porous carbon derived from a two-dimensional Cu-MOF, showing 196 F g -1 In general, the capacitance performance of existing carbon materials needs to be improved, and they cannot provide high specific capacitance to meet the ever-expanding energy needs of modern society. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing an N-doped Zn-MOF-derived carbon skeleton material, which has a large specific surface area, a large graded porosity, contains N atom doping, and has excellent capacitance performance.

[0005] A second object of the present invention is to provide a supercapacitor having excellent capacitance performance.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing an N-doped Zn-MOF-derived carbon skeleton material comprises the following steps:

[0008] 1) reacting the zinc source and the organic ligand in a solvent, separating the solid and the liquid, and drying the solid to obtain Zn-MOF;

[0009] 2) calcining Zn-MOF at 700-950° C. under a protective atmosphere to obtain Zn-MOF-C;

[0010] 3) After mixing Zn-MOF-C and urea, calcining at 700-900° C. under a protective atmosphere to obtain N-doped Zn-MOF-derived carbon skeleton material Zn-MOF-CN; the mass ratio of the Zn-MOF-C to urea is 1:4-1:12.

[0011] The preparation method of the N-doped Zn-MOF-derived carbon skeleton material of the present invention firstly adopts a zinc source and an organic ligand to construct an accordion-shaped prismatic nanorod Zn-MOF, then obtains a layered structure composed of graphene nanosheets after carbonization and calcination, and finally adopts urea for N-doping. The obtained N-doped Zn-MOF-derived carbon skeleton material has a high specific surface area, hierarchical porosity and abundant active sites, and can provide excellent capacitance performance. On the one hand, urea acts as a nitrogen source to provide N atoms for N doping. On the other hand, it can act as an activator and pore expander, infiltrating into the interlayers of Zn-MOF-C nanorods and etching away some carbon atoms to increase the interlayer spacing. The appropriate use of urea can increase the specific surface area and pore size of the N-doped Zn-MOF-derived carbon skeleton material Zn-MOF-CN, allowing micropores and mesopores to coexist inside Zn-MOF-CN and improve the hierarchical porosity of Zn-MOF-CN. In addition, the gasification and expansion of urea can break the edges of the layered carbon structure of Zn-MOF-CN into tiny graphene-like nanosheets, further increasing the specific surface area of ​​Zn-MOF-CN and providing abundant active sites.

[0012] Preferably, in step 1), the zinc source is zinc acetate dihydrate, and the organic ligand is curcumin; the mass ratio of the zinc source to the ligand is 6:10 to 12:10.

[0013] Preferably, the reaction in step 1) is first carried out at room temperature for 4 to 5 hours, and then heated to 60 to 90° C. for 48 to 96 hours.

[0014] In order to promote the formation of Zn-MOF materials, preferably, the solvent in step 1) is a mixed solvent of dimethylacetamide and anhydrous ethanol; the volume ratio of dimethylacetamide to anhydrous ethanol is 3:1 to 5:1.

[0015] Preferably, in step 2), the calcination time is 2 to 5 hours.

[0016] In order to ensure the quality of N atom doping and prevent the collapse of the carbon pore structure, preferably, in step 3), the mass ratio of the Zn-MOF-C to urea is 1:8.

[0017] Preferably, in step 3), the calcination time is 2 to 5 hours.

[0018] A supercapacitor comprises a supercapacitor electrode and an electrolyte, wherein the electrode material of the supercapacitor electrode is an N-doped Zn-MOF-derived carbon skeleton material prepared by the above preparation method.

[0019] Since the N-doped Zn-MOF-derived carbon skeleton material has a high specific surface area, hierarchical porosity and abundant active sites, the supercapacitor of the present invention has excellent capacitance performance.

[0020] Preferably, the supercapacitor is a button-type symmetrical supercapacitor, and the electrolyte is an electrolyte.

[0021] Preferably, the supercapacitor is a flexible micro-supercapacitor based on interdigital electrodes, and the electrolyte is a gel electrolyte made of polyvinyl alcohol, H3PO4 and water.

[0022] Since N-doped Zn-MOF-derived carbon skeleton materials have certain flexibility and still have stable capacitance performance under different denaturation conditions, N-doped Zn-MOF-derived carbon skeleton materials have good application prospects in miniaturized electronic products. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Chemical structure analysis of Zn-MOF and related materials, wherein (a) is the XRD pattern of Zn-MOF, Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3, and (b) is the Raman spectrum of Zn-MOF, Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3;

[0024] Figure 2 The pore structures of Zn-MOF-C and Zn-MOF-CN, wherein (a) is the N2 adsorption / desorption isotherms of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3, and (b) is the pore size distribution of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3;

[0025] Figure 3 SEM images and TEM images of Zn-MOF, wherein (a, b) are SEM images of Zn-MOF, and (c, d, e) are TEM images of Zn-MOF;

[0026] Figure 4 It is the Fe-SEM image of Zn-MOF-C;

[0027] Figure 5 Fe-SEM images of Zn-MOF-CN, wherein (a, b) are Fe-SEM images of Zn-MOF-CN1, (c, d) are Fe-SEM images of Zn-MOF-CN2, and (e, f) are Fe-SEM images of Zn-MOF-CN3;

[0028] Figure 6TEM images, HRTEM images and EDS mapping images of Zn-MOF-CN, wherein (a, b, c) are TEM images, HRTEM images and EDS mapping images of Zn-MOF-CN1, (d, e, f) are TEM images, HRTEM images and EDS mapping images of Zn-MOF-CN2, and (g, h, i) are TEM images, HRTEM images and EDS mapping images of Zn-MOF-CN3;

[0029] Figure 7 Electrochemical characterization of different electrode materials in the three-electrode system, where (a) is the electrochemical characterization of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 at 5 mV s -1 CV curves of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 at 0.25Ag -1 (c) is the GCD curve of Zn-MOF-CN2 at different scan rates, (d) is the GCD curve of Zn-MOF-CN2 at different current densities, (e) is the specific capacitance of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 at different current densities, (f) is the AC impedance diagram of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3;

[0030] Figure 8 Figure 2 is the electrochemical characterization of button-type symmetric supercapacitors, where (a) is the CV curves of Zn-MOF-CN2 button-type symmetric supercapacitors at different scan rates, (b) is the GCD curves of Zn-MOF-CN2 button-type symmetric supercapacitors at different current densities, (c) is the specific capacitance of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 symmetric supercapacitors at different current densities, (d) is the Ragone plot of Zn-MOF-CN2 button-type symmetric supercapacitors related to energy-power density, and (e) is the specific capacitance of Zn-MOF-CN2 button-type symmetric supercapacitors at 2Ag -1 Cyclic stability performance diagram below;

[0031] Fig. 9Electrochemical characterization of flexible micro-supercapacitors, where (a) is a digital image of the interdigitated MSC of the flexible micro-supercapacitor, (b) is the CV curve of the Zn-MOF-CN2 flexible micro-supercapacitor at different scan rates, (c) is the GCD curve of the Zn-MOF-CN2 flexible micro-supercapacitor at different current densities, and (d) is the area and volume specific capacitance of the Zn-MOF-CN2 flexible micro-supercapacitor at different current densities;

[0032] Fig.10 Electrochemical tests of flexible micro supercapacitors under bending and parallel / series conditions, where (a) is the CV curve of Zn-MOF-CN2 flexible micro supercapacitors at different bending angles, and (b) is the CV curve of Zn-MOF-CN2 flexible micro supercapacitors at 20 mV s -1 CV curves of two Zn-MOF-CN2 flexible micro-supercapacitors in series and in parallel at different scan rates;

[0033] Fig.11 It is the charge and discharge cycle performance test and energy density test of the flexible micro supercapacitor, where (a) is the constant current charge and discharge cycle performance diagram of the Zn-MOF-CN2 flexible micro supercapacitor, and (b) is the Ragone diagram (lit LED diagram) of the Zn-MOF-CN2 flexible micro supercapacitor. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.

[0035] 1. Embodiment of the method for preparing the N-doped Zn-MOF-derived carbon skeleton material of the present invention

[0036] Example 1

[0037] The preparation method of the N-doped Zn-MOF derived carbon skeleton material of this embodiment specifically comprises the following steps:

[0038] 1) Curcumin (600 mg) and zinc acetate dihydrate (540 mg) were added to a mixed solvent of dimethylacetamide (40 mL) and anhydrous ethanol (10 mL). After stirring at room temperature for 4 h, the solution was heated in a pressure bottle in an oil bath at 75 °C for 72 h; finally, the resulting suspension was centrifuged and washed with DMF several times, and then vacuum dried at 60 °C overnight to obtain Zn-MOF.

[0039] 2) Zn-MOF was placed in a porcelain boat and heated in a tube furnace at 40 mL min under nitrogen atmosphere. -1 The heating rate during the calcination process was 2℃min -1, the temperature was raised to 900 °C and maintained for 2 h. After calcination, the temperature was naturally cooled to room temperature under a nitrogen atmosphere to obtain Zn-MOF-derived carbon (Zn-MOF-C).

[0040] 3) 0.5 g Zn-MOF-C and urea were mixed in a mortar at a ratio of 1:4, and after being fully ground, they were transferred to a porcelain boat and calcined at 800 °C for 2 h in a constant temperature tube furnace under a nitrogen atmosphere. After calcination, the mixture was naturally cooled to room temperature under a nitrogen atmosphere to obtain a N-doped Zn-MOF-derived carbon skeleton material, named Zn-MOF-CN1.

[0041] Example 2

[0042] The preparation method of the N-doped Zn-MOF-derived carbon skeleton material of this embodiment is different from that of Example 1 in that: Step 3) 0.5 g of Zn-MOF-C and urea are mixed in a mortar at a ratio of 1:8. Finally, the N-doped Zn-MOF-derived carbon skeleton material is obtained, which is named Zn-MOF-CN2.

[0043] Example 3

[0044] The preparation method of the N-doped Zn-MOF-derived carbon skeleton material of this embodiment is different from that of Example 1 in that: 3) 0.5 g of Zn-MOF-C and urea are mixed in a mortar at a ratio of 1:12. Finally, the N-doped Zn-MOF-derived carbon skeleton material is obtained, which is named Zn-MOF-CN3.

[0045] 2. Embodiments of the Supercapacitor of the Present Invention

[0046] Example 4

[0047] The supercapacitor of this embodiment is a button-type symmetrical supercapacitor, and its preparation process is as follows: 80wt% Zn-MOF-CN, 10wt% carbon black and 10wt% polyvinylidene fluoride are mixed and dispersed in 200μL of N-methyl-2-pyrrolidone. The resulting uniform slurry is applied to the surface of nickel foam as a working electrode. Two working electrodes with the same mass of coated active material are selected, and the two electrodes are separated by a polypropylene film as a diaphragm. The electrolyte is a 6M KOH solution, and assembled into a symmetrical button-type device (shell model CR2032) under a pressure of 20MPa.

[0048] Example 5

[0049] The supercapacitor of this embodiment is a flexible micro supercapacitor based on interdigital electrodes, and its preparation process is as follows: Zn-MOF-CN2 dispersion (0.5 mg·mL -1), directly prepare micro-supercapacitor electrodes by mask-assisted filtration; the obtained interdigitated electrodes are transferred to a flexible polyethylene terephthalate (PET) substrate, and the edges of the interdigitated electrodes are connected to copper tapes with the help of conductive silver paste, and then the gel electrolyte prepared by 1 g PVA, 1 g H3PO4 and 10 mL deionized water is drop-coated on the interdigitated electrodes, and the micro-supercapacitor is dried in air for 24 h.

[0050] 3. Experimental Examples

[0051] Experimental Example 1: Chemical structure and composition of materials

[0052] The chemical structures of Zn-MOF, Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 were analyzed by XRD. Figure 1 (a). The Zn-MOF prepared by the present invention shows characteristic peaks consistent with the reported Zn-MOF at 2θ=9.5°, 10.6°, 14.3°, 21.7° and 24°. The calcined and nitrogen-doped Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 of the present invention show a broad diffraction peak at 23° and an inconspicuous diffraction peak at 42.5°, which are respectively attributed to the (002) and (101) crystal planes of carbon (JCPDS No.41-1487).

[0053] Raman spectroscopy was used to analyze Zn-MOF, Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3. The results are as follows: Figure 1 (b) As shown. Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 of the present invention all show obvious D band (1340cm -1 ) and G band (1580cm -1 ), which is attributed to the defective graphitic carbon structure and the C-C bond sp 2 The intensity ratio of the two bands in the Raman spectrum (I D / I G ) can reflect the degree of graphitization. D / I G is 1.095, while the I D / I G are 1.118, 1.131 and 1.135 respectively. D / I GThe value increases significantly, which means that more defects and more active sites are beneficial for the application of supercapacitors.

[0054] Experimental Example 2: Pore structure of materials

[0055] N2 adsorption / desorption isothermal tests were performed on Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3, and the results are as follows: Figure 2 As shown in (a). The Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 of the present invention all show the characteristics of type I and type IV isothermal adsorption-desorption curves. At very low pressures (P / P0<0.05), Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 all show a sharp increase in adsorption capacity, indicating the presence of abundant micropores. However, the Zn-MOF-C sample shows a narrower H3 hysteresis loop, while all N-doped samples Zn-MOF-CN show wider H3 hysteresis loops. Hysteresis loops can be found in the isotherms at medium relative pressures (P / P0=0.4-0.9), confirming the presence of abundant mesopores. The significant increase in mesopores proves that urea as a nitrogen source for N doping can be used as an activation and pore expansion agent for porous carbon. As shown Figure 2 As shown in Fig. 2a, the pore size distribution curve shows that the micropores (<2nm) and mesopores (2-50nm) of the Zn-MOF-CN sample coexist. The above analysis shows that all Zn-MOF-CN samples of the present invention are hierarchically porous. Micropores can provide a large specific surface area and thus provide a high specific capacitance, and mesopores can act as a "highway" to promote the rapid transmission of electrolyte ions to the inside of the carbon material. These structural features will contribute to the Zn-MOF-CN sample of the present invention having a high specific capacitance and excellent rate performance.

[0056] In addition, the specific surface area of ​​Zn-MOF-C of the present invention is 730.8 m 2 g -1 The specific surface areas of Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 obtained after N doping are 1149.3 m 2 g -1 、1163.9m 2 g -1 and 1129m 2 g -1 , which is consistent with the trend of pore size increasing first and then decreasing, which once again confirms the role of urea as an activator and pore expander. The above results also show that the appropriate use of urea can increase the surface area and pore size, which is beneficial to the electrochemical performance of supercapacitors. Excessive use will cause the carbon pore structure to collapse, resulting in a decrease in specific surface area.

[0057] Experimental Example 3: Material morphology analysis

[0058] 1) Analysis of the morphology of Zn-MOF

[0059] The surface morphology of Zn-MOF of the present invention was analyzed by SEM and TEM. Figure 3 As shown. The Zn-MOF of the present invention presents an accordion-like prismatic nanorod structure, but with different lengths and widths, with multiple layers stacked together, and some fragments layered on the surface of the column. The TEM image further shows the accordion shape of the Zn-MOF of the present invention, and the magnified TEM image shows a porous serrated structure, in which the light color implies the high porosity of the Zn-MOF.

[0060] 2) Analysis of the morphology of Zn-MOF-C

[0061] The surface morphology of Zn-MOF-C of the present invention was analyzed by SEM, and the results are as follows: Figure 4 Compared with Zn-MOF, the morphology of Zn-MOF-C of the present invention does not change much, and after high-temperature calcination, it still presents the morphology of accordion-shaped prismatic nanorods, indicating the stability of the Zn-MOF structure.

[0062] 3) Analysis of the morphology of Zn-MOF-CN

[0063] The morphology of Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 of the present invention was analyzed by SEM. Figure 5 As shown. Figure 5 (a, b) It can be seen that Zn-MOF-CN1 shows a clearer layered structure, indicating that urea should play the role of a chemical activator. It has been reported in the literature that urea can enhance the "in situ etching" of the activator to form porosity. Therefore, during the N-doping process, urea penetrates into the interlayer of the Zn-MOF-C nanorods and etches away some carbon atoms, resulting in a larger interlayer spacing and a clearer layered structure. Comparing the SEM images of Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3, it can be found that when the Zn-MOF-C / urea ratio changes (from 1:4 to 1:8, and finally to 1:12), the layered structure undergoes a process from thick to thin and then thick again. It can be explained that the increase in the amount of urea is conducive to the activation and etching of the layered carbon structure, resulting in a clearer layered structure and a larger interlayer spacing. However, excessive use of urea will lead to the collapse of the layered structure.

[0064] 4) Structure and elemental composition of Zn-MOF-CN

[0065] The structures and elemental compositions of Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 of the present invention were further determined by using TEM and EDS mapping images. Figure 6 As shown. Figure 6 (ai) It can be seen that Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3 have many tiny graphene nanosheets located at the thin edges, indicating that the nanorods are composed of many tiny graphene nanosheets. The existence of graphene nanosheets can be proved by the d space of 0.34nm, which can be found in Figure 6 The 0.34 nm lattice of graphene nanosheets can be clearly seen in the HR-TEM images of Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3 samples shown in (c, f, i), which is consistent with the Raman ( Figure 1 b) The results are consistent. Peng et al. (Peng H., Ma G., Sun K., et al. Afacile and rapid preparation of highly crumpled nitrogen-doped graphene-like nanosheets for high-performance supercapacitors [J]. Journal of Materials Chemistry A, 2015, 3 (25): 13210-13214) synthesized a highly crumpled nitrogen-doped graphene-like nanosheet using a macroporous resin. They proposed that during the high-temperature heat treatment, urea gasification and expansion enhanced the structure of graphene-like nanosheets. Therefore, the layered carbon structure of Zn-MOF-CN was broken into tiny graphene-like nanosheets by urea gasification and expansion. EDS mapping of Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3 samples proved that the N element was uniformly distributed on the Zn-MOF-CN nanorods, indicating that N doping was successful. EDS mapping results confirmed the uniform distribution of N and O elements on the carbon matrix.

[0066] Experimental Example 4: Electrochemical Testing and Characterization of Materials

[0067] 1) Electrochemical testing of electrodes of different materials

[0068] The specific capacitance of the working electrode is calculated based on the charge-discharge curve as follows:

[0069] 80wt% Zn-MOF-CN, 10wt% carbon black and 10wt% polyvinylidene fluoride were mixed and dispersed in 200μL of N-methyl-2-pyrrolidone. The resulting uniform slurry was coated on the surface of nickel foam as a working electrode. The prepared working electrode was dried at 80℃ in a vacuum for 12h. At the same time, Hg / HgO and Pt sheets were used as reference electrodes and counter electrodes, respectively. Electrochemical measurements were tested in a three-electrode cell at ambient temperature using an electrochemical workstation (CHI 760E) with 6M KOH as the electrolyte. In addition, constant current charge and discharge (GCD) tests were performed using a CT2001ALAND Cell test system. Specific capacitance (C1, F g -1 ) is measured based on the GCD curve of the test according to equation (1):

[0070]

[0071] Here, I, m, Δt, and ΔV represent the discharge current (A), active material mass (g), discharge time (s), and voltage drop (V).

[0072] Due to the large specific surface area, high graded porosity and N atom doping of Zn-MOF-CN, Zn-MOF-CN samples have great potential applications as electrodes for supercapacitors. In order to evaluate the potential application of the prepared porous carbon samples as supercapacitor electrodes, the electrochemical properties of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 electrodes were first tested using CV, GCD and EIS in a three-electrode 6M KOH solution electrode system. The results are shown in Figure 2. Figure 7 shown.

[0073] like Figure 7 As shown in (a), the CV curves of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3 electrodes are all approximately rectangular, reflecting good symmetry and capacitance characteristics. Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3 electrodes show a larger response current than the Zn-MOF-C electrode, indicating that the specific surface area increases and the specific capacitance increases after nitrogen doping. Among the three doping ratios, the Zn-MOF-CN2 electrode shows the largest response current. As mentioned above, appropriately increasing the amount of urea can increase the specific surface area, enhance N doping and a larger pore size, thereby improving the performance of the supercapacitor, but when the urea is too much, it will cause the carbon pore structure to collapse, which means that the surface area is reduced and the pore size becomes smaller, resulting in a decrease in the performance of the supercapacitor. As Figure 7 As shown in (b), the specific capacitances of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2, and Zn-MOF-CN3 are 193 F g-1 、208Fg -1 , 261F g -1 and 233F g -1 The Zn-MOF-CN2 electrode shows the longest GCD time, which is consistent with the largest CV curve area. Figure 7 As shown in (c), all CV curves of Zn-MOF-CN2 at different scan rates show similar approximately rectangular profiles without obvious distortion, indicating fast charge transfer capability and excellent rate performance. Figure 7 (d) shows that Zn-MOF-CN2 has a high stability in the range of 0.25 to 20 A g -1 The GCD curves are highly symmetrical at current densities of 2.5 and 1.5 nm, indicating excellent capacitor performance and good electrochemical reversibility.

[0074] Figure 7 (e) shows the specific capacitance of different electrodes at different current densities. -1 At a current density of 2.5 Å, the capacitance is as high as 293.3 F g -1 When the current density increases to 20A g -1 When the specific capacitance is still 187F g -1 , the capacitance retention rate is about 63.6%, showing its good rate capability. These values ​​are significantly higher than those of Zn-MOF-C, Zn-MOF-CN1 and Zn-MOF-CN3. The specific capacitance values ​​of Zn-MOF-CN2 electrode are comparable to or even higher than those of other carbon materials reported previously (Table 1). EIS tests are used to measure the kinetic behavior of carbon materials, such as Figure 7 As shown in (f), the equivalent series resistances of Zn-MOF-C, Zn-MOF-CN1, Zn-MOF-CN2 and Zn-MOF-CN3 are 2.90, 1.55, 1.29 and 1.39Ω, respectively. It can be found that the AC impedance diagrams of all electrodes have smaller semicircular arcs in the high-frequency region and nearly vertical lines in the low-frequency region, which means that this series of materials has smaller charge transfer resistance and better capacitive behavior. Considering its optimized N doping content, specific surface area and pore size distribution, the Zn-MOF-CN2 sample shows the best capacitive performance.

[0075] Table 1 Specific capacitance values ​​of different electrodes

[0076]

[0077]

[0078] References:

[0079] [1]Li Z.-X.,Yang B.-L.,Zou K.-Y.,et al.Novel porous carbon nanosheetderived from a 2D Cu-MOF:Ultrahigh porosity and excellent performances in thesupercapacitor cell[J].Carbon,2019,144:540-548.

[0080] [2]Ping Y.,Yang S.,Han J.,et al.N-self-doped graphitic carbonaerogels derived from metal–organic frameworks as supercapacitor electrodematerials with high-performance[J].Electrochimica Acta,2021,380:138237.

[0081] [3]Duan H.-H.,Bai C.-H.,Li J.-Y.,et al.Temperature-DependentMorphologies of Precursors:Metal–Organic Framework-Derived Porous Carbon forHigh-Performance Electrochemical Double-Layer Capacitors[J].InorganicChemistry,2019,58(4):2856-2864.

[0082] [4]Gu Y.,Miao L.,Yin Y.,et al.Highly N / O co-doped ultramicroporouscarbons derived from nonporous metal-organic framework for high performancesupercapacitors[J].Chinese Chemical Letters,2021,32(4):1491-1496.

[0083] [5]Zhang D., Zhang J., Pan M., et al. Necklace-like C-ZIF-8@MWCNTsfabricated by electrochemical deposition towards enhanced supercapacitor[J]. Journal of Alloys and Compounds, 2021,853:157368.

[0084] [6]Shang Z., An

[0085] [7]Ran F., Yang X., Xu

[0086] 2) Electrochemical performance of button-type symmetrical supercapacitors

[0087] The electrochemical performance test voltage window range of the button-type symmetrical supercapacitor is 0-1 V. The specific capacitance, energy density and power density of the button-type symmetrical supercapacitor are calculated based on the charge and discharge curves as follows:

[0088]

[0089]

[0090]

[0091] Where C2 is (F g -1) is the specific capacitance of the Zn-MOF-CN symmetric supercapacitor; I (A) is the current; Δt (s) is the discharge time; m (mg) is the total mass of the active material; ΔV (V) is the voltage window; E (Wh kg -1 ) is the energy density; P (W kg -1 ) is the power density.

[0092] To further characterize the electrochemical properties of the Zn-MOF-CN2 electrode, a button-type symmetrical supercapacitor was assembled using 6M KOH electrolyte, and the electrochemical properties of the button-type symmetrical supercapacitor were analyzed. Figure 8 As shown. Figure 8 (a) It can be seen that in the scanning rate range of 5 to 200 mV s -1 When the CV curve is 0-1 V, it shows a typical rectangular shape, indicating a fast electrochemical response in the electrolyte solution. Even at high scan rates, the CV shape is mirror-symmetrical, indicating the high reversibility of the sample. -1 , to evaluate the energy and power density of button-type symmetric supercapacitors, such as Figure 8 b. All GCD curves show typical linear discharge curves, indicating low internal resistance. Figure 7 The capacitance of the symmetrical supercapacitor is calculated according to equation (2): Figure 8 (c) The symmetric device of Zn-MOF-CN2 electrode shows 126.5F g -1 (at 0.25A g -1 Hours) and 106.4F g -1 (at 20A g -1 The results show that the Zn-MOF-C, Zn-MOF-CN1 and Zn-MOF-CN3 electrodes have high capacitance values ​​(at 200 ℃ and 100 ℃) and have a high capacitance retention rate (84.11%). These values ​​are also significantly higher than those of Zn-MOF-C, Zn-MOF-CN1 and Zn-MOF-CN3 electrodes.

[0093] Figure 8 d shows the Ragone plot of the button-type symmetric supercapacitor related to energy-power density. -1 Zn-MOF-CN2 button-type symmetrical supercapacitor at 250W kg -1 The power density was 17.57Wh kg -1 In addition, when the current density is 20A g -1 When the power density increases to 20kW kg -1 The energy density of the button-type symmetrical supercapacitor remains at 14.78 W h kg-1 To further demonstrate its potential in supercapacitors, Zn-MOF-CN2 button-type symmetric supercapacitors were tested at 2A g -1 Cycling at high current density, such as Figure 8 After 40,000 GCD cycles, the Zn-MOF-CN2 button-type symmetric supercapacitor still retains more than 94.45% of the initial specific capacitance, proving that Zn-MOF-CN2 is an ideal candidate material for button-type supercapacitors.

[0094] 3) Electrochemical performance of flexible micro-supercapacitors

[0095] The electrochemical performance test of the micro supercapacitor was carried out on a CHI 760E electrochemical workstation with a potential window of 0 to 1 V. The area specific capacitance, volume specific capacitance, energy density and power density of the flexible micro supercapacitor were calculated based on the charge and discharge curves as follows:

[0096]

[0097]

[0098]

[0099]

[0100] Among them, C A Yes (mF cm -2 ) is the area specific capacitance; J (mA cm -2 ) is the current density; Δt(s) is the discharge time; C V Yes (F cm -3 ) is the volume specific capacitance; d (mm) is the thickness of the device; E A (μWh cm -2 ) is the area energy density; P A (μW cm -2 ) is the area power density.

[0101] The rapid development of portable / wearable electronics has put forward new demands for flexible, intelligent and sustainable energy storage devices. Micro supercapacitors (MSCs) show great potential as an indispensable power source for miniaturized electronic applications due to their advantages such as high power density, fast charge / discharge rate and long life. In order to determine the performance of Zn-MOF-CN2 as a flexible electrode material, an organic filter membrane was used as the substrate and H3PO4-PVA gel was used as the solid electrolyte. Flexible interdigitated electrodes were prepared by mold-assisted vacuum filtration, and the electrochemical performance of button-type symmetrical supercapacitors was analyzed. The results are shown in Figure 2. Fig. 9 shown.

[0102] Depend on Fig. 9 (a) It can be seen that the flexible interdigitated device consists of four positive electrodes and four negative electrodes. In order to evaluate the electrochemical performance of the prepared flexible micro supercapacitor, the -1 The CV test was carried out at a scan rate of 1000 nm and a voltage window of 0-1 V. The results are shown in Fig. 9 (b) shows that even at 50mV s -1 At high scan rates, the CV curves showed only slight changes, indicating the rapid transport of electrolyte ions and excellent rate performance. This may be attributed to the high specific surface area, hierarchical porosity, and abundant active sites of the Zn-MOF-CN2 electrode material. -2 GCD tests were performed at various current densities within a range of 1.5 Å to further evaluate the capacitive properties of flexible MSCs based on Zn-MOF-CN2, such as Fig. 9 As shown in (c), all GCD curves are symmetrical and approximately triangular, indicating excellent rate performance. The area specific capacitance is calculated from the GCD curve, as shown in Fig. 9 As shown in d, Zn-MOF-CN2-based flexible MSCs were -2 When the -2 High area specific capacitance and 1.5F cm -3 Even if the current density increases to 100 μA cm -2 When the area specific capacitance of Zn-MOF-CN2 based flexible MSCs is 15.8 mF cm -2 , the volumetric capacitance remains at 0.6F cm -3 , which indicates that Zn-MOF-CN2-based flexible MSCs have excellent rate performance.

[0103] To further evaluate the application potential of Zn-MOF-CN2 in flexible electronic systems, flexible MSCs based on Zn-MOF-CN2 were tested under bending and parallel / series conditions. Fig.10 As shown in (a), the CV curves at different bending angles show a high degree of overlap, demonstrating its stable capacitance performance under deformation conditions. Fig.10 The illustration of a further confirms that the flexible MSCs based on Zn-MOF-CN2 can maintain their normal structure and flexibility at different bending angles of 0°, 30°, 60° and 90°, indicating excellent flexibility. Fig.10As shown in (b), the total specific capacitance and working voltage can be adjusted by connecting Zn-MOF-CN2 flexible MSCs in parallel or in series. When two Zn-MOF-CN2 flexible MSCs are connected in series, the voltage doubles. When two Zn-MOF-CN2 flexible MSCs are connected in parallel, the response current and capacitance double, showing the superior integration ability of Zn-MOF-CN2 flexible MSCs.

[0104] The constant current charge-discharge cycle performance of the Zn-MOF-CN2-based MSCs device was investigated. Fig.11 As shown in (a), the device retains 76.56% of its initial capacitance after 5000 cycles. Fig.11 (b) It can be seen that the MSCs devices based on Zn-MOF-CN2 have good thermal conductivity at 20, 25 and 50 μW cm -2 The power densities are 5.8, 4 and 2.19 μWh cm -2 Energy density. In order to more intuitively demonstrate the good electrochemical performance of MSCs devices based on Zn-MOF-CN2, connecting two MSCs devices in series can light up a red light-emitting diode (LED), showing good energy storage performance. These results indicate the potential application of Zn-MOF-CN2 materials in miniaturized electronic products.

Claims

1. A method for preparing a N-doped Zn-MOF-derived carbon skeleton material, characterized in that: The following steps are involved: 1) reacting the zinc source and the organic ligand in a solvent, separating the solid and the liquid, and drying the solid to obtain Zn-MOF; 2) calcining Zn-MOF at 700-900° C. under a protective atmosphere to obtain Zn-MOF-C, and the calcination time is 2 h; 3) After mixing Zn-MOF-C and urea, calcining them at 700-800° C. under a protective atmosphere to obtain N-doped Zn-MOF-derived carbon skeleton material Zn-MOF-CN, the calcination time is 2 h; the mass ratio of the Zn-MOF-C and urea is 1:4-1:12; the zinc source in step 1) is zinc acetate dihydrate, the organic ligand is curcumin, and the mass ratio of the zinc source and the ligand is 6:10-12:

10.

2. The method for preparing the N-doped Zn-MOF derived carbon skeleton material according to claim 1, characterized in that: The reaction in step 1) is first carried out at room temperature for 4 to 5 hours, and then heated to 60 to 90° C. for 48 to 96 hours.

3. The method for preparing the N-doped Zn-MOF derived carbon skeleton material according to claim 1 or 2, characterized in that: The solvent in step 1) is a mixed solvent of dimethylacetamide and anhydrous ethanol; the volume ratio of dimethylacetamide to anhydrous ethanol is 3:1 to 5:

1.

4. The method for preparing the N-doped Zn-MOF derived carbon skeleton material according to claim 1, characterized in that: In step 3), the mass ratio of Zn-MOF-C to urea is 1:

8.

5. A supercapacitor, characterized in that: It comprises a supercapacitor electrode and an electrolyte, wherein the electrode material of the supercapacitor electrode is an N-doped Zn-MOF-derived carbon skeleton material prepared by the preparation method according to any one of claims 1 to 4.

6. The supercapacitor according to claim 5, characterized in that: The supercapacitor is a button-type symmetrical supercapacitor, and the electrolyte is an electrolyte.

7. The supercapacitor according to claim 5, characterized in that: The supercapacitor is a flexible micro-supercapacitor based on interdigital electrodes, and the electrolyte is a gel electrolyte made of polyvinyl alcohol, H3PO4 and water.